Turning Strategies into Actions: Integrated Land Use and Transport Planning in Western Australia - Curtis, Carey (1999)
The focus of this paper is on the contribution of land use planning to the achievement of balanced transport outcomes. The paper reviews the current planning strategies and processes and puts forward a range of measures which could assust in turning strategies into actions and therefore into implementation. The suggestions for action are based upon research and experience of current international planning practice, and include action in the three areas of planning policy, planning applications ans assessment, and the players involved in planning.